Beschilderungskonzept Radverkehr. Neubeschilderung der Radwege. Projektinformation. Konzeption und Zielspinnen. - (:unkn) unknown (My University, 2005)
By order of the city of Waiblingen this pocket timetable was developed. It is a low-priced, compact and plain aid to get information about the local public transport of a town. It contains the complete information to plan a individual journey and connects the plan of public transport network with the timetable. The pocket timetable is an ideal supplement to existing timetables. difu
Keywords: Beschilderung; Freizeitverkehr; Verkehrssicherheit; Bestandsaufnahme; Individualverkehr; Radwegenetz; Radverkehrsbeschilderung; Fahrradförderung; Fahrradtourismus; Fahrradinfrastruktur; Fahrradwegweisung; Konzeption